HUBUNGAN RELIGIUSITAS DENGAN KEBERMAKNAAN HIDUP PADA PENGGUNA NAPZA YANG SEDANG MENJALANI REHABILITASI DI LEMBAGA PENCEGAHAN PENYALAHGUNAAN NARKOTIKA BHAYANGKARA INDONESIA (LRPPN – BI) MEDAN - Dwi Nursiti; Indo Mora; Siska Dwi Ningsih; Lorena Sinambela (JURNAL PSYCHOMUTIARA, 2021)
Narcotics can make people who use it forget everything important in their lives such as forgetting who they are, the people closest to them, far from their religion and worship and losing what is the meaning of life that they have trusted before using narcotics. Therefore, religious or religious guidance is highly prioritized in a rehabilitation institution to regrow the meaning of life of the narcotics user who was lost due to a wrong decision for using narcotics which made him far from religion and also far from the meaning of life. This study was conducted with the title religiosity relationship with the meaningfulness of life on drug users who are undergoing rehabilitation at the Bhayangkara Narcotics Abuse Prevention Rehabilitation Institute (LRPPN-BI) Medan with a sample of 30 people, this study was conducted using a quantitative approach. Data collection techniques using a questionnaire with a Likert scale model. The data obtained were analyzed using the SPSS Version 22 program. The results showed there was no relationship between religiosity and the meaningfulness of life of drug users who were undergoing rehabilitation with a very weak / low correlation category (no correlation).